Genome-wide RAD sequencing data provide unprecedented resolution of the phylogeny of temperate bamboos (Poaceae: Bambusoideae) - Wang, Xueqin (Sci Rep, 2017)
The temperate bamboos (tribe Arundinarieae, Poaceae) are strongly supported as monophyly in recent molecular studies, but taxonomic delineation and phylogenetic relationships within the tribe lack resolution. Here, we sampled 39 species (36 temperate bamboos and 3 outgroups) for restriction-site associated DNA sequencing (RAD-seq) with an emphasis on Phyllostachys clade and related clades. Using the largest data matrix for the bamboos to date, we were able to infer phylogenetic relationships with unparalleled resolution. The Phyllostachys, Shibataea, and Arundinaria clades defined from plastid phylogeny, were not supported as monophyletic group. However, the RAD-seq phylogeny largely agreed with the morphology-based taxonomy, with two clades having leptomorph rhizomes strongly supported as monophyletic group. We also explored two approaches, BWA-GATK (a mapping system) and Stacks (a grouping system), for differences in SNP calling and phylogeny inference. For the same level of missing data, the BWA-GATK pipeline produced much more SNPs in comparison with Stacks. Phylogenetic analyses of the largest data matrices from both pipelines, using concatenation and coalescent methods provided similar tree topologies, despite the presence of missing data. Our study demonstrates the utility of RAD-seq data for elucidating phylogenetic relationships between genera and higher taxonomic levels in this important but phylogenetically challenging group.